The Effect of Augmented Reality and Virtual Reality Media on Affective Characteristics (Interest, Motivation, and Attitude) in Chemistry Learning: A Literature Review - Maya Sari; Muntholib; Habiddin; I Wayan Dasna; Sumari (Orbital: The Electronic Journal of Chemistry)
This study aims to analyze the effect of Augmented Reality (AR) and Virtual Reality (VR) media on motivation, interest, and attitude in chemistry learning. Sampling was selected by searching the ERIC database (eric.ed.gov) covering the last five years. Articles were sourced from journals ranging from quartile 1 to quartile 4, resulting in a total of 20 collected articles. Analyses were carried out based on affective characteristics, specifically motivation, interest, and attitude, within the context of chemistry learning using AR and VR media. The study’s findings indicate that AR and VR media significantly impact these affective factors, revealing an interrelationship between motivation, interest, and attitude in the learning process.